Marine hotspots of activity inform protection of a threatened community of pelagic species in a large oceanic jurisdiction. (25th March 2020) - Requena, S.; Oppel, S.; Bond, A. L.; Hall, J.; Cleeland, J.; Crawford, R. J. M.; Davies, D.; Dilley, B. J.; Glass, T.; Makhado, A.; Ratcliffe, N.; Reid, T. A.; et al.
Abstract: Remote oceanic islands harbour unique biodiversity, especially of species that rely on the marine trophic resources around their breeding islands. Identifying marine areas used by such species is essential to manage and limit processes that threaten these species. The Tristan da Cunha territory in the South Atlantic Ocean hosts several endemic and globally threatened seabirds, and pinnipeds; how they use the waters surrounding the islands must be considered when planning commercial activities. To inform marine management in the Tristan da Cunha Exclusive Economic Zone (EEZ), we identified statistically significant areas of concentrated activity by collating animal tracking data from nine seabirds and one marine mammal. We first calculated the time that breeding adults of the tracked species spent in 10 × 10 km cells within the EEZ, for each of four seasons to account for temporal variability in space use. By applying a spatial aggregation statistic over these grids for each season, we detected areas that are used more than expected by chance. Most of the activity hotspots were either within 100 km of breeding colonies or were associated with seamounts, being spatially constant across several seasons. Our simple and effective approach highlights important areas for pelagic biodiversity that will benefit conservation planning and marine management strategies. Abstract : Tristan da Cunha, a remote group of islands in the South Atlantic Ocean, hosts several endemic and globally threatened pelagic vertebrates; identifying the marine areas that such species use is critical when planning maritime commercial activities that could threaten their populations and in the design of appropriate conservation measures. To identify hotspots of pelagic activity we collated the tracking data from nine seabirds and one pinniped to identify hotspots of pelagic activity. Combining a time‐in‐area approach with spatial analysis techniques involving indicators of spatial association (Moran's I and Getis‐Ord G*), we revealed areas that are used more than expected by chance within the EEZ. Most of these activity hotspots are found either within 100 km of the islands or associated with seamounts and are spatially constant across several seasons. We present a simple and effective approach to single out important areas of pelagic biodiversity for the benefit of marine management strategies and conservation planning elsewhere.